(untitled) (The International Journal of Educational Sciences and Arts, 2025)
This study examines the linguistic errors made by first-year dental students at Al-Razi University, Yemen, in English for Medical Purposes (EMP) courses. It aims to identify and analyze common challenges in spelling, syntax, parts of speech, synonyms, and medical terminology. Adopting a mixed-methods approach, the study collected data through mid-term exams and qualitative observations. Errors were categorized and analyzed to determine their frequency and underlying causes. The study assessed the prevalence of different linguistic errors and students’ difficulties in understanding and applying medical English terminology and grammar. The findings indicate that spelling errors were the most common (27.81%), followed by syntactic errors (13.46%) and synonym-related errors (12.63%). Qualitative observations further highlighted students’ struggles with medical vocabulary and grammatical structures, impacting their overall language proficiency. The study underscores the importance of a strong foundation in general English for successful EMP learning. It recommends targeted instructional strategies, including comprehensive grammar training, interactive exercises, and real-world language applications. The findings provide insights for improving EMP teaching methodologies to enhance students’ academic performance and preparedness for medical professions. Future research should explore similar challenges in other medical disciplines to refine effective teaching approaches and contribute to better healthcare communication.